Protective effect of resveratrol against naphthalene-induced oxidative stress in mice - BECEREN, AYFER; ÇETİNEL, ŞULE (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2008)
Objective: This investigation confirms the role of free radicals in naphthalene-induced toxicity and elucidates the mechanism of resveratrol (RVT). Methods: Both male and female BALB-c mice were administered with naphthalene (100mg/kg, i.p.) for 30 days, either along with saline or along with RVT (10 mg/kg, orally). At the end of the experiment, following treatment and sacrifice of animals by decapitation, lung, liver and kidney tissue samples were taken for histological examination or determination of malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO) activity and collagen contents. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), blood urea nitrogen (BUN) and creatinine levels and lactate dehydrogenase (LDH) activity were measured in the serum samples, while TNF-alpha, IL-beta, IL-6 and total antioxidant capacity (AOC) were assayed in plasma samples. Results: Naphthalene administration caused a significant decrease in tissue GSH and plasma AOC, which was accompanied with significant increases in tissue MDA and collagen levels and MPO activity. Moreover, the pro-inflammatory mediators (TNF-alpha, IL-beta, IL-6), LDH activity, AST, ALT, creatinine and BUN levels were significantly increased in the naphthalene group. On the other hand, RVT treatment reversed all these biochemical indices as well as histopathological alterations induced by naphthalene. Conclusions: Oxidative mechanisms play an important role in naphthalene-induced tissue damage, and RVT, by inhibiting neutrophil infiltration, balancing oxidant-antioxidant status, and regulating the generation of inflammatory mediators, ameliorates oxidative organ injury due to naphthalene toxicity. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: naphthalene; resveratrol; lipid peroxidation; glutathione; myeloperoxidase; WINE CONSTITUENT POLYPHENOL; AQUEOUS GARLIC EXTRACT; RED WINE; INDUCED TOXICITY; TISSUE-DAMAGE; VITAMIN-E; RATS; GLUTATHIONE; MECHANISM; MELATONIN